2014
DOI: 10.1186/s13099-014-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low Helicobacter pylori prevalence in North Sulawesi, Indonesia and identification of a Maori-tribe type strain: a cross sectional study

Abstract: BackgroundSulawesi in Indonesia has a unique geographical profile with assumed separation from Sundaland. Studies of Helicobacter pylori in this region are rare due to the region’s rural location and lack of endoscopy equipment. Indirect methods are, therefore, the most appropriate for measuring H. pylori infection in these areas; with the disposable gastric brush test, we can obtain gastric juice as well as small gastric tissue samples for H. pylori culture. We investigated the prevalence of H. pylori infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…This prevalence was lower compared to similar study in India by Sodhi et al and in China by Xu et al 13,14 The prevalence of H. pylori infection in this study was higher compared to several previous studies in North Sulawesi, Surabaya, and Jakarta which were 14.3%, 11.5%, and 9.5%, respectively. 15,16,17 The demography of population with H. pylori infection in this study was similar to those of several previous studies which stated that low economic status, densely populated area, not clean water, smoking, and alcohol consumption were strongly correlated with the presence of H. pylori infection.…”
Section: Discussionsupporting
confidence: 88%
“…This prevalence was lower compared to similar study in India by Sodhi et al and in China by Xu et al 13,14 The prevalence of H. pylori infection in this study was higher compared to several previous studies in North Sulawesi, Surabaya, and Jakarta which were 14.3%, 11.5%, and 9.5%, respectively. 15,16,17 The demography of population with H. pylori infection in this study was similar to those of several previous studies which stated that low economic status, densely populated area, not clean water, smoking, and alcohol consumption were strongly correlated with the presence of H. pylori infection.…”
Section: Discussionsupporting
confidence: 88%
“…The overall H . pylori prevalence was only 14.3% for adults and 3.8% for children [ 11 ]. However our results cannot be generalized across Indonesia due to the difference of host factor and environmental condition.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study using 5 different diagnostic methods confirmed that the prevalence of H. pylori infection in Surabaya (Java island) was low (only 11.5 %) [ 18 ]. We also found a low prevalence of H. pylori infection in a minor group of North Sulawesi; the prevalence was only 14.3 % for adults and 3.8 % for children [ 19 ]. However, it remains unclear whether the low incidence of gastric cancer in Indonesia is due to low infection rates only or also owing to low H. pylori pathogenicity.…”
Section: Introductionmentioning
confidence: 99%